Enhancing Students' Speaking Ability at SMK Jagakarsa Through The Application of Role Play Technique - Siti Rodiyah; Ditta Mustika R.; Lili Wahdini; Deny Gunawan S.; Lestari, Anggie Tri (CV. Ulil Albab Corp, 2024)
This study aimed to enhance the speaking proficiency of students through the implementation of the role-play technique, employing Classroom Action Research (CAR). The research targeted the X-Ph grade students at SMK Jagakarsa during the 2023 academic year, comprising 38 students. The investigation unfolded over two cycles, each encompassing planning, action, observation, and reflection phases. Quantitative data, derived from pre-test and post-test results, were employed for analysis. The findings revealed a notable improvement in students' speaking abilities through the utilization of the role-play technique. The mean score for the pre-test was 67.21, which increased to 72.21 in post-test I and further to 78.52 in post-test II. This upward trend in scores indicated enhanced performance in the second cycle compared to the first. The percentage of students scoring above 75 points also exhibited growth, with 5 students (13.16%) surpassing this threshold in the pre-test, 16 students (42.11%) in post-test I, and 30 students (78.95%) in post-test II. Overall, the students demonstrated significant improvement in speaking ability, progressing from the initial meeting to subsequent sessions.